Impact of Material Type and Relative Humidity on the Survival of Escherichia coli, Listeria monocytogenes, and Salmonella enterica on Harvest Bags - Cyril A. Etaka; Daniel L. Weller; Tuan Le; Alexis Hamilton; Faith J. Critzer; Laura K. Strawn (Journal of Food Protection)
Harvest bags, if not properly cleaned and sanitized, can serve as sources of microbial contamination, making it vital to understand pathogen survival on these surfaces to inform sanitation best practices. The study objective was to assess the survival of generic Escherichia coli, Listeria monocytogenes, and Salmonella enterica on harvest bag materials: 100% canvas, nylon, and Cordura. Coupons from each material were inoculated with rifampicin-resistant strains of E. coli or rifampicin-resistant 5-strain cocktails of L. monocytogenes or S. enterica at ca. 7.3 ± 0.1 log CFU/coupon. Coupons were air-dried until the inoculum was visibly dry and held at 22°C under different relative humidity (RH) conditions: 30 or 80% RH for E. coli (90 d) and 55% RH for L. monocytogenes and S. enterica (21 d). E. coli concentration was enumerated at 12 time-points: 0, 1.5, 4, and 8 h, and 1, 2, 3, 7, 14, 30, 60, and 90 d post-inoculation. L. monocytogenes and S. enterica levels were enumerated at 10 time-points: 0, 1, 4, and 8 h, and 1, 2, 3, 7, 14, and 21 d. Coupons were massaged for 60 s with 20 mL of 0.1% peptone and plated in duplicate on selective and non-selective media in triplicate experiments with triplicate replicates (n = 9). Models were fitted to describe bacterial die-off in log CFU/coupon over time. E. coli exhibited a triphasic die-off with a faster rate of die-off on nylon surfaces. S. enterica demonstrated greater die-off on Cordura compared to canvas, and L. monocytogenes followed a biphasic die-off, with no significant difference in survival across the materials. Findings indicate E. coli survival was influenced by RH, time, and material, with the fastest die-off on nylon materials. S. enterica die-off was influenced by material and time with a faster die-off on Cordura. L. monocytogenes exhibited similar die-off on canvas and Cordura. Sanitization of harvest bags is recommended to reduce contamination risks as pathogen survival can be influenced by bag material and environmental conditions.